The Fiqh of ḥayḍ, istiḥāḍah, and nifās: a simple guide for Muslim women - Karim, Fatimah (Mission Soft Foundation, 2025)
Among the most important discussions in Islamic jurisprudence related to women are the rulings of ḥayḍ (menstruation), istiḥāḍah (irregular or non-menstrual bleeding), and nifās (post-natal bleeding). These natural occurrences are part of women’s lives, yet they have significant implications on worship such as ṣalāh (prayer), ṣawm (fasting), ṭahārah (purification), and even marital relations. The jurists (fuqahāʾ) have written extensively on these subjects, as they combine aspects of ritual law (ʿibādāt) and personal matters (muʿāmalāt). Correct understanding of these rulings is essential for Muslim women in order to fulfill their obligations in accordance with Sharīʿah while appreciating the mercy and wisdom of Allah in granting concessions (rukhaṣ).